An increase in regulatory T cells in peripheral blood correlates with an adverse prognosis for malignant melanoma patients – A study of T cells and natural killer cells - Nanna Heldager Pedersen; Helene Bjerregaard Jeppesen; Gry Persson; Sophie Bojesen; Thomas Vauvert F. Hviid (Current Research in Immunology, 2024)
Malignant melanoma is a highly immunogenic tumour, and the immune profile significantly influences cancer development and response to immunotherapy. The peripheral immune profile may identify high risk patients. The current study showed reduced levels of CD4+ T cells and increased levels of CD8+ T cells in peripheral blood from malignant melanoma patients compared with controls. Percentages of peripheral CD56dimCD16+ NK cells were reduced and CD56brightCD16−KIR3+ NK cells were increased in malignant melanoma patients. Late stage malignant melanoma was correlated with low levels of CD4+ T cells and high levels of CD56brightCD16−KIR3+ NK cells. Finally, high levels of Tregs in peripheral blood were correlated with poor overall survival and disease-free survival. The results indicate that changes in specific immune cell subsets in peripheral blood samples from patients at the time of diagnosis may be potential biomarkers for prognosis and survival. Further studies will enable clarification of independent roles in tumour pathogenesis.